2010
DOI: 10.1148/radiol.10092388
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional Study of Tracheomegaly in Children after Fetal Tracheal Occlusion for Severe Congenital Diaphragmatic Hernia

Abstract: Purpose:To measure tracheal dimensions in children with congenital diaphragmatic hernia (CDH) who had undergone fetoscopic endoluminal tracheal occlusion (FETO) or were treated expectantly during gestation. Materials and Methods:The study was approved by the local ethics committee.Computed tomography was performed in 23 patients (14 boys and nine girls) aged 1 month to 6.5 years, and the anteroposterior diameter, width, area, and perimeter of the trachea were determined. Seven of the 23 patients had undergone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…However, the neonates and infants do have tracheomegaly that does not seem to have an obvious clinical impact, except for a barking cough on effort [54,55]. Over time, the widening seems to become less important [55].…”
Section: Summary Of Outcomesmentioning
confidence: 99%
“…However, the neonates and infants do have tracheomegaly that does not seem to have an obvious clinical impact, except for a barking cough on effort [54,55]. Over time, the widening seems to become less important [55].…”
Section: Summary Of Outcomesmentioning
confidence: 99%
“…Tracheomegaly has been described in human fetuses undergoing FETO [20,35,36,37]. In humans this effect has been linked to the coexistence of the hypoplastic bronchial tree [38] and the effect of the occlusion itself [36,39].…”
Section: Discussionmentioning
confidence: 99%
“…Within this group, we identified 105 infants (Type 1A) who had undergone fetal endoscopic tracheal occlusion (FETO) as therapy for antenatally diagnosed severe congenital diaphragmatic hernia [12,13]. Previously, it was thought that only placement of the FETO balloon early in the gestation would result in TBM, [14] however, one study demonstrated that even infants receiving the occlusion after 26 weeks gestation still developed TBM [12].…”
Section: Are There Distinct Clinical Sub-types Of Tbm?mentioning
confidence: 99%
“…Previously, it was thought that only placement of the FETO balloon early in the gestation would result in TBM, [14] however, one study demonstrated that even infants receiving the occlusion after 26 weeks gestation still developed TBM [12]. The tracheal diameters normalize by the fifth year of life [13].…”
Section: Are There Distinct Clinical Sub-types Of Tbm?mentioning
confidence: 99%